Building pathways out of poverty through climate smart agriculture and effective targeting. Issue 7 (3rd October 2018) - Hellin, Jon; Fisher, Eleanor
ABSTRACT: One focus of agricultural development is climate smart agricultural technologies and practices (CSA). Development practitioners invest in scaling these to have wider impact. Ineffective targeting stymies CSA's contribution to poverty reduction by excluding many of the poor and/or including those for whom agriculture is not a pathway out of poverty. This viewpoint proposes the need to recognise differentiated livelihood pathways within smallholder agriculture, linked to farmers' differential capacity to engage in climate risk management. A farmer and livelihoods typology provides a framework to improved targeting of CSA and to identifying where alternative interventions, such as social protection, are more appropriate.